Increasing maneb doses induces reactive oxygen species overproduction and nephrotoxicity in adult mice. (13th June 2017) - Jaballi, Imen; Ben Saad, Hajer; Bkhairia, Intidhar; Kammoun, Intissar; Droguet, Michael; Magné, Christian; Boudawara, Tahia; Kallel, Choumous; Nasri, Monsef; Hakim, Ahmed; Ben Amara, Ibtissem
Abstract: Background and purpose: The aim of this study was to elucidate the biochemical, molecular and histopathological aspects of the kidney injuries as well as the hematological perturbations induced after adult mice exposure to increasing doses of maneb (MB). Material and method: Adult mice were intraperitoneally treated for seven days with four graded doses of MB, corresponding to 1/8, 1/6, 1/4 and 1/2 of its lethal dose (LD50 =1500 mg/kg body weight). Results: Hematological analysis revealed a significant disruption in total white blood cells and platelets and a significant decrease in the plasmatic levels of ferrozine in mice treated with 1/8, 1/6 and 1/4 of MB LD50 . However, the ferrozine levels increased significantly in the group treated with 1/2 of MB LD50 . Evenly, our results showed a significant increase in the levels of malondialdehyde, lipid hydroperoxides, hydrogen peroxide and advanced oxidation protein products in all treated groups. The activities of catalase and glutathione peroxidase decreased significantly in all MB treated mice. Additionally, all treated groups exhibited strong nephrotoxicity signs, including increases in plasma urea, creatinine and albumin levels and lactate dehydrogenase activity, as well as a significant decrease in uric acid levels. Electrophoresis analysis revealed nucleic acid degradation, testifying the genotoxicity of MB. Moreover, the histopathological observations showed severe renal injuries, which could be related to the above mentioned data. Conclusions: Our data showed, for the first time, that the MB tested doses led to oxidative stress installation causing renal cell damages and lowering all defense systems capacities.